2021
DOI: 10.1158/1078-0432.ccr-20-1420
|View full text |Cite
|
Sign up to set email alerts
|

Circulating T-cell Immunosenescence in Patients with Advanced Non–small Cell Lung Cancer Treated with Single-agent PD-1/PD-L1 Inhibitors or Platinum-based Chemotherapy

Abstract: Purpose: CD28, CD57, and KLRG1 have been previously identified as markers of T-cell immunosenescence. The impact of immunosenescence on anti-PD(L)-1 (ICI) or platinum-based chemotherapy (PCT) in patients with advanced non–small cell lung cancer (aNSCLC) is unknown. Experimental Design: The percentage of CD28−, CD57+, KLRG1+ among CD8+ T cells [senescent immune phenotype (SIP)] was assessed by flow cytometry on blood from pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 52 publications
6
85
1
2
Order By: Relevance
“…Therefore, the frequency of senescent T cells may act as a potential biomarker to predict the response to ICIs. In advanced NSCLC and melanoma patients treated with PD-1/PD-L1 inhibitors, a high level of circulating senescent CD8 + T cells, with limited proliferative capacity and lower IL-2 and higher TNF-α and IFN-γ production [68] , was significantly correlated with resistance to ICIs [69] and a poor overall response rate (ORR), median PFS and OS [68 , 70] .…”
Section: Potential Prognostic Biomarkers In Cancer Treatmentmentioning
confidence: 99%
“…Therefore, the frequency of senescent T cells may act as a potential biomarker to predict the response to ICIs. In advanced NSCLC and melanoma patients treated with PD-1/PD-L1 inhibitors, a high level of circulating senescent CD8 + T cells, with limited proliferative capacity and lower IL-2 and higher TNF-α and IFN-γ production [68] , was significantly correlated with resistance to ICIs [69] and a poor overall response rate (ORR), median PFS and OS [68 , 70] .…”
Section: Potential Prognostic Biomarkers In Cancer Treatmentmentioning
confidence: 99%
“…As V and C140 dosages found to significantly improve CI preclinical activity are suitable for a combinatorial use in cancer patients, clinical trials in TNBC and B-cell lymphoma are now planned to confirm the efficacy of this “two-hit” plus CI therapy. It will be of interest to investigate in enrolled patients a number of emerging candidate biomarkers of immune cell activation, including: a) APC activation patterns; b) the generation of new TCF1 + stem-like CD8+ T-cells; c) CXCL13 and CCR5 overexpressing, neo-antigen reactive CD8+ T cells [ 8 ]; d) newly generated IFN-γ–expressing resident memory T cells [ 9 ]; e) pre-treatment values of senescent CD28-CD57+KLGR1+CD8+ T cells [ 10 ]; and f) post-treatment values of proliferating PD-1+CD8+ T cells [ 11 ]. The goal of such a therapy, in fact, is the generation of a long-lasting anti-tumor immunity in treated cancer patients.…”
mentioning
confidence: 99%
“…In contrary to the previous meta-analysis, we observed the better survival outcomes only in patients < 75 years, but not in patients ≥ 75 years. It had been reported that aging is associated with immune dysregulation, such as the decreased TCR diversity in CD4+ T cells (14) and CD8+ T cells (15), but not the T-cell immunosenescence (29). In addition, aging-associated adipocyte accumulation in the bone marrow also contributes to reduced hematopoiesis with age (30), and hematopoiesis becomes skewed toward myeloid and away from lymphoid lineages with age (16).…”
Section: Discussionmentioning
confidence: 99%